how to train your dragon book 9 : how to steal a dragon's sword - Cowell, Cressida; Cressida Cowell (New York Hachette Book Group, 2012)
Hiccup faces a dragon rebellion (the Red-Rage) while attempting to win a dangerous sword-fighting contest to become King of the Wilderwest. Amidst rising, stormy seas and attacking dragons, Hiccup must overcome Alvin the Treacherous and a witch's prophecy to save humanity.
English